CRITICAL ANALYSIS ON THE IMPACT OF GREEN HUMAN RESOURCES MANAGEMENT PRACTICES ON PERFORMANCE OF HEALTHCARE MANAGEMENT. - ‏Salem Saleh Bani Humayyim, ‏Samer Ibrahim Osrah, IbraheemQasimBagawi, ‏DhaifallahAmmashAlotaibi, Omar Talal Omar Alyafei, Adel MokkeledAlmutairi, ObaidJamaan Abdullah Alzahrani, Ahmed Atiah Ahmed Alzahrani, (Chelonian Research Foundation, 2023)
This article highlights the GreenResourcesManagement (GHRM) significance on well-being. With expanding mindfulness of its effect on natural supportability and corporate hones, GHRM has gotten an imperative perspective of human Resources Management in numerous businesses, including refining. This article investigates the standards of GHRM, analyzes its suggestions for healthcare, and assesses its effect on organizational execution, especially healthcare management Through a comprehensive audit of existing writing, this article gives an in-depth consideration of the challenges and openings for executing GHRM hones in healthcare and suggestions for future investigations and benefits for healthcare organizations. Key words: Green Human Resources Management (GHRM), HealthcareMetrics, OrganizationalPerformance. EnvironmentalImpact, Sustainable Human Resource Management (SHRM), Resource-Based View (RBV), EmployeeEngagement, GreenInitiatives, EnvironmentalAwareness, OperationalEfficiency, RegulatoryCompliance, StakeholderCollaboration, PerformanceMetrics, Organizational Culture